Analisis Kualitas Perairan Pesisir Teluk Tomini Terhadap Aktivitas Pemukiman Dan Pariwisata Di Provinsi Gorontalo - Siti Amalia Gobel; Farid SM; Farina Gonibala (Universitas Negeri Gorontalo, 2025)
The coastal waters of Tomini Bay in Gorontalo Province play an important role in supporting marine ecosystems and socio-economic activities, particularly coastal settlements and tourism. The rapid development of these activities has the potential to exert pressure on coastal water quality if not managed sustainably. This study aims to analyze the quality of coastal waters in Tomini Bay and examine the influence of settlement and tourism activities on coastal water conditions. The research method employed is a literature study approach by reviewing scientific publications, research reports, and relevant policy documents. The analysis was conducted using a descriptive qualitative method focusing on physical, chemical, and biological water quality parameters and the impacts of human activities. The results indicate that settlement activities contribute to increased pollution loads through domestic waste, while tourism activities affect water quality through waste from tourism facilities and pressure on coastal ecosystems. Therefore, integrated and sustainable coastal management strategies are required to maintain the quality of coastal waters in Tomini Bay, Gorontalo Province.